2000
DOI: 10.1038/sj.bmt.1702506
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis after hematopoietic stem cell transplantation: incidence, clinical characteristics and outcome

Abstract: Summary:A national survey of tuberculosis after hematopoietic stem cell transplant (SCT) was undertaken to study incidence, clinical presentation and outcome. Twenty confirmed cases were found among 8013 patients (eight in 5147 autologous and 12 in 2866 allogeneic SCT). The estimated incidence in cases/10 5 patients/year (95% CI) was 101 (56.5-145) for the whole group, 71.1 (21.8-120) in autologous and 135.6 (58.9-212) in allogeneic transplants. Compared with the general population, tuberculosis was more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 30 publications
(53 reference statements)
4
85
2
1
Order By: Relevance
“…A high incidence of tuberculosis might be Tuberculosis after RI-UCBT T Maeda et al expected in RI-UCBT patients due to patients' age and prolonged immunosuppression associated with the use of CB as a stem cell source; however, the incidence of tuberculosis following RI-UCBT was comparable to that following allo-HSCT in previous reports from endemic countries. 15,[18][19][20][21] Tuberculosis is less frequent in RI-UCBT recipients than in the immunodeficient patients of different etiologies such as solid organ transplantation and AIDS. Immunosuppression after RI-UCBT is transient, 11 while AIDS patients and solid organ transplant recipients have a life-long immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high incidence of tuberculosis might be Tuberculosis after RI-UCBT T Maeda et al expected in RI-UCBT patients due to patients' age and prolonged immunosuppression associated with the use of CB as a stem cell source; however, the incidence of tuberculosis following RI-UCBT was comparable to that following allo-HSCT in previous reports from endemic countries. 15,[18][19][20][21] Tuberculosis is less frequent in RI-UCBT recipients than in the immunodeficient patients of different etiologies such as solid organ transplantation and AIDS. Immunosuppression after RI-UCBT is transient, 11 while AIDS patients and solid organ transplant recipients have a life-long immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent studies on tuberculosis following allogeneic hematopoietic stem cell transplantation (allo-SCT) have demonstrated that this is a significant problem in endemic countries with an incidence of 0.1-5.5%. [13][14][15][16][17][18][19][20][21] This is the first report, to our knowledge, on tuberculosis following RI-UCBT. Detailed description of this complication would be informative in the management of RI-UCBT.…”
mentioning
confidence: 99%
“…1,2 Although Mycobacterium tuberculosis (TB) infection is uncommon in UCBT recipients, few available reports [3][4][5] suggest a more severe clinical course as compared with the TB infections in auto-and allo-SCT recipients. [6][7][8] Here, we report a case of TB following UCBT and discuss its clinical characteristics and challenges.…”
mentioning
confidence: 99%
“…The clinical course of TB in recipients of UCBT is therefore very different from TB in other hematopoietic SCT (HSCT) recipients. Whereas the median TB onset time in auto-and allo-SCT recipients is about 279 and 257 days, respectively, 6,7 it is only about 50 days in UCBT recipients; on the basis of the data extracted from the literature. In addition, in either autologous or allogeneic recipients, TB tends to be localized and mainly involves the lungs, whereas in UCBT recipients TB is almost all disseminated with very high mortality.…”
mentioning
confidence: 99%
“…However, several centres have reported a varying and often surprisingly low incidence of this disease even in endemic populations, with no reported cases of Mycobacterium bovis, apart from disseminated bacille Calmette-Guerin. [1][2][3] A 31-year-old Mexican woman was diagnosed with AML when she was admitted with a 2-week history of fevers above 38 1C and neutropenia. Four years before, she had been treated for severe acquired aplastic anaemia with antithymocyte globulin and other immunosuppressants.…”
mentioning
confidence: 99%